Evaluation of The Determinants of Domestic Bonds in Ghana - Zahra Moro; Oscar Agyemang Opoku (iRASD Journal of Management)
The study sought to examine the determinants domestic bonds in Ghana using secondary data. The researcher used the Government of Ghana bonds issued in 2013 to 2017 and has not matured by 31st December 2019. A sample of 6 Government of Ghana bonds which have been on the secondary market for at least two years with a tenor of at least three years was used by the researcher. Based on the stationary and the existence on cointegration vectors, the study investigated long and short run effects using ARDL (1,0,1,1,1,1) and ARDL (1,2,2,2,2,2) Error Correction Models respectively. The E-Views version 11 was used to conduct the analysis. It was found that GDP had a long run insignificant positive effect on Ghana Government Bond Prices, but a short run significant positive effect on Ghana Government Bond Prices. The second major finding was that Exchange Rate had a significant positive effect on Ghana Government Bond Prices in the long run, but this significant effect was negative in the short run. Thirdly, it was revealed that inflation had a significant negative effect on Ghana Government Bond Prices both in the long and short run. Risk Free Rate of Return had a significant negative effect in the long run but had insignificant effect in the short run. Monetary Policy Rate had significant positive effects in the long and short run. It was concluded that increases in Exchange Rate, Gross Domestic Products and monetary policy led to corresponding increases in the prices of government bonds while increases in Inflation, and Risk Free Rate of Return led to a decrease in the prices of Government bonds. In the short run, an increase in Exchange Rate and Inflation leads to a decrease in bond prices while an increase GDP, Risk Free Rate of Return and Monetary Policy Rate leads to a corresponding increase in bond prices. It is recommended that investors consider inflation, GDP, exchange rate, Risk Free Return and Monetary Policy, among other factors, when making decisions on the position to take in a bond as it determines bond prices. Policymakers should aim at working to achieving low inflation and exchange rate figures as that will increase bond prices and make it more attractive to foreign investors. It is also important that policy makers understand and manage effectively risk free bonds and the monetary policy as they have significant effects on the prices of government bonds.